202k views
5 votes
Help solve pls fast
it's a maths question ​

Help solve pls fast it's a maths question ​-example-1

2 Answers

0 votes

Answer:


1/x

Explanation:

To simplify, work from the inside out.

We start with


\sqrt[4]{x^(3/4)}

on the inside. And we can change the fourth root into a fractional exponent -- 1/4:


(x^{(3)/(4))^(1/4)

A power of a power means multiply the exponents, giving


x^{(3)/(4) * (1)/(4)} = x^(3/16)

So now we have


[(x^(3/16))^(-4/3)]^4

From here, apply the "power of a power rule" again, working from the inside out.


(x^(-12/48))^4


x^(-48/48)


x^(-1)

or


1/x

User Jimmiesrustled
by
6.1k points
4 votes

Answer:

Explanation:


[(\sqrt[4]{x^{(3)/(4)}})^{(-4)/(3)} ]^(4)


= [(x^{(3)/(4)*(1)/(4)})^{(-4)/(3)}]^(4)\\\\\\= [(x^{(3)/(16) ) ^{(-4)/(3)}}]^(4)\\\\=[ x^{(3)/(16)*(-4)/(3)}]^(4)\\\\=[x^{(-1)/(4)}]^(4)\\\\=x^{(-1)/(4)*4}\\\\=x^(-1)\\\\=(1)/(x)

Hint:


(a^(m))^(n)=a^(m*n)

User Eng Yew
by
5.4k points